Zn‐Catalyzed [3+2]‐Annulation Strategy: Straightforward Access to Aminoalkyl Indolizines. Issue 39 (10th October 2019) - Li, Junxuan; Yang, Daji; Wang, Hua; Zhu, Baofu; Cao, Hua
Abstract : An efficient Zn‐catalyzed [3+2]‐annulation strategy for the synthesis of aminoalkyl indolizines has been developed. The three‐component domino reaction of 2‐(pyridin‐2‐yl)acetates, ynals and amines proceeds smoothly with high efficiency to afford the indolizines in good yields. This transformation may facilitate the development of new synthetic methods for the efficient and sustainable construction of aminoalkyl indolizines in an atom‐economic way from simple, abundant starting materials. Abstract : Indolizine was widely found in a large variety of substances that exhibit important biological activities and broad applications in drugs and organic material. A novel and efficient strategy for the synthesis of aminoalkyl indolizines by ZnCl2 ‐catalyzed three‐component reaction of 2‐(pyridin‐2‐yl)acetates, ynals and amines.